Band Engineering via Gradient Molecular Dopants for CsFA Perovskite Solar Cells. (24th February 2021) - Huang, Ziru; Wei, Mingyang; Proppe, Andrew Harald; Chen, Hao; Chen, Bin; Hou, Yi; Ning, Zhijun; Sargent, Edward
Abstract: Perovskites with the multi‐cation composition of cesium (Cs), methylammonium (MA), and formamidinium (FA) (CsMAFA) are pursued for their high power conversion efficiencies, but they are limited by their thermal stability. To withstand damp‐heat accelerated aging MA‐free compositions such as CsFA are of interest, but these exhibit lower carrier diffusion lengths and thus lesser performance in photovoltaic devices. A band engineering strategy that overcomes limited carrier diffusion within inverted perovskite solar cells based on CsFA is reported. A joint experimental‐computational study shows that treating the perovskite with an n‐type molecular dopant increases band bending, shaping the electric field across the active layer to overcome limited diffusive transport. Using this strategy, CsFA solar cell devices with stabilized power conversion efficiencies of 20.3%, a high value for devices using CsFA active layers, are fabricated. Abstract : To enable highly efficient and stable CsFA perovskite solar cells, a joint experimental–computational study is conducted. It is shown that by treating the perovskite with an n‐type molecular dopant, the band bending is increased, shaping the electric field across the active layer to overcome limited diffusive transport. Using this strategy, CsFA solar cell devices are fabricated with stabilized power conversion efficiencies of 20.3%.